Utilizing sinapic acid as an inhibitory antiviral agent against MERS-CoV PLpro - Mudassar Shahid; Ahmed L. Alaofi; Mushtaq Ahmad Ansari; Sheikh Fayaz Ahmad; Saleh Alsuwayeh; Ehab Taha; Mohammad Raish (Elsevier, 2024)
Concerns about the social and economic collapse, high mortality rates, and stress on the healthcare system are developing due to the coronavirus onslaught in the form of various species and their variants. In the recent past, infections brought on by coronaviruses severe acute respiratory syndrome coronaviruses (SARS-CoV and SARS-CoV-2) as well as middle east respiratory syndrome coronavirus (MERS-CoV) have been reported. There is a severe lack of medications to treat various coronavirus types including MERS-CoV which is hazard to public health due to its ability for pandemic spread by human-to-human transmission. Here, we utilized sinapic acid (SA) against papain-like protease (PLpro), a crucial enzyme involved in MERS-CoV replication, because phytomedicine derived from nature has less well-known negative effects. The thermal shift assay (TSA) was used in the current study to determine whether the drug interact with the recombinant MERS-CoV PLpro. Also, inhibition assay was conducted as the hydrolysis of fluorogenic peptide from the Z-RLRGG-AMC-peptide bond in the presence of SA to determine the level of inhibition of the MERS-CoV PLpro. To study the structural binding efficiency Autodock Vina was used to dock SA to the MERS-CoV PLpro and results were analyzed using PyMOL and Maestro Schrödinger programs. Our results show a convincing interaction between SA and the MERS protease, as SA reduced MERS-CoV PLpro in a dose-dependent way IC50 values of 68.58 μM (of SA). The TSA showed SA raised temperature of melting to 54.61 °C near IC50 and at approximately 2X IC50 concentration (111.5 μM) the Tm for SA + MERS-CoV PLpro was 59.72 °C. SA was docked to MERS-CoV PLpro to identify the binding site. SA bound to the blocking loop (BL2) region of MERS-CoV PLpro interacts with F268, E272, V275, and P249 residues of MERS-CoV PLpro. The effectiveness of protease inhibitors against MERS-CoV has been established and SA is already known for broad range biological activity including antiviral properties; it can be a suitable candidate for anti-MERS-CoV treatment.